The H+-Translocating Inorganic Pyrophosphatase From Arabidopsis thaliana Is More Sensitive to Sodium Than Its Na+-Translocating Counterpart From Methanosarcina mazei - Pérez-Castiñeira, José R.; Serrano, Aurelio (Frontiers in Plant Science, 2020)
Overexpression of membrane-bound K+-dependent H+-translocating inorganic pyrophosphatases (H+-PPases) from higher plants has been widely used to alleviate the sensitivity towards NaCl in these organisms, a strategy that had been previously tested in Saccharomyces cerevisiae. H+-PPases from different organisms have been reported to functionally complement the yeast cytosolic soluble pyrophosphatase (IPP1). Here, the efficiency of the K+-dependent Na+-PPase from the archaea Methanosarcina mazei (MVP) and its H+-pumping plant-type counterpart from Arabidopsis thaliana (AVP1) to functionally complement in vivo IPP1 has been compared. Both membrane-bound integral PPases (mPPases) performed equally well under normal growth conditions, however, under salt stress MVP was significantly more efficient than AVP1 at functionally complementing IPP1. The subcellular distribution of the heterologously-expressed mPPases was crucial in order to observe the phenotypes associated with the complementation. In vitro studies showed that the PPase activity of MVP was less sensitive to Na+ than AVP1. Consistently, when MVP-expressing yeast cells were grown in the presence of NaCl only a marginal increase in their internal PPi levels was observed with respect to control cells. By contrast, yeast cells expressing AVP1 had significantly higher levels of this metabolite under the same conditions. The H+-pumping activity of AVP1 was also markedly inhibited by Na+ in vitro. Our results suggest that mPPases act primarily by hydrolysing the PPi generated in the cytosol when expressed in yeast, and that AVP1 is more susceptible to Na+ inhibition both in vivo and in vitro than MVP. Based on this experimental evidence we propose Na+-PPases as biotechnological tools to generate salt-tolerant plants.